I, fly : the buzz about flies and how awesome they are - Heos, Bridget (Henry Holt and Company, 2015)
Fly is fed up with everyone studying butterflies. After all, flies go through metamorphosis too -- and they are so much cooler! They flap their wings 200 times a second, compared to a butterfly's measly five to twelve times. Their babies -- maggots -- are much cuter than caterpillars (obviously). And when they eat solid food, they even throw up on it to turn it into a liquid. Who wouldn't want to study an insect like that?